Kedudukan Anak Luar Kawin Dalam Pewarisan Suku Minangkabau Ditinjau Dari Hukum Waris Adat - Riska Suainur Sona; Aurelia Agatha; Nilam Permata Sari; Nur Fajarriah Indah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The status of extramarital children can be grouped into three kinship systems in Indonesia, namely patrilineal kinship, matrilineal kinship, and patrilineal kinship. The position of an extramarital child according to customary law is not the position of heirs or natural heirs of the father's descendants. Extramarital children only have a relationship with their mother and relatives. However, related to the context of the Supreme Court case law and the Constitutional Court decision Number 46/PUU-VIII/2010, this is an opportunity for extramarital children to get inheritance and legal protection from suspected biological fathers. So even an unrecognized extramarital child automatically has a civil relationship with his mother and his mother's family. Thus, the necessity of a mother to recognize her extramarital child as mentioned in the Burgerlijk Wetboek is no longer necessary. Likewise, it has been affirmed in the Constitutional Court Decision Number 46 / PUU-VIII / 2010 which is also part of legal reform, so that the child also has a juridical relationship with his biological father if it can be proven based on science technology and / or other evidence according to law.